Application Modes Affect Two Universal Adhesive Systems' Nanoleakage Expression and Shear Bond Strength. (30th September 2021) - Bakry, A. S.; Abbassy, M. A.
Abstract : Objectives . The aim of this study was to evaluate the shear bond strength and the nanoleakage expression of CLEARFIL Universal Bond Quick and Tetric N-Bond adhesive systems bonded to dentin. Materials and Methods . 100 freshly extracted human premolar teeth were utilized. The teeth were sectioned to expose dentin. All dentin specimens were assigned into 4 experimental groups; 2 groups had Universal Bond Quick (Universalself group) and Tetric N-Bond (Tetricself group) applied in the self-etch mode, while 2 groups had Universal Bond Quick (Universaltotal group) and Tetric N-Bond (Tetrictotal group) applied in the total-etch mode. n = 15 for shear bond strength and n = 10 for nanoleakage experiment. One-way ANOVA and Kruskal-Wallis test were utilized to analyze the shear bond strength test and the nanoleakage expression, respectively. Results . The highest significant bond strength value was recorded by the Tetricself specimens (p < 0.05 ) when compared to the remaining three groups. There were no statistically significant differences between the shear bond strength values recorded in the Tetrictotal, Universalself, and Universaltotal groups (p < 0.05 ). Both bonding systems applied in the self-etch mode (Universalself, Tetricself ) had no silver nitrate deposits in the hybrid layer and the hybrid layer-adhesive interface (p < 0.001 ); however, both bonding systems applied in the total-etch mode (Universaltotal, Tetrictotal ) had silver nitrate deposits in the hybrid layer, the hybrid layer-adhesive interface, and the bonding layer (p < 0.001 ). Conclusion . Applying the Universal Bond Quick and Tetric N-Bond in the self-etch mode exhibited better results in terms of nanoleakage expression. Universal Bond Quick showed the stability of the shear bond strength to dentin when applied using the total-etch or self-etch modes. Tetric N-Bond showed significant deterioration in bond strength when applied in the total-etch mode and exhibited the highest bond strength when applied in the self-etch mode.